Aneurysm following ligation of patent ductus arteriosus: myth or reality?. (February 2013) - Malhotra, Amber; Gupta, Shyam; Kaushal, Ram Prasad; Sharma, Praveen; Moolchand, Songra
Complications following ligation of a patent ductus arteriosus are rare and require careful evaluation. We report one case that highlights the clinical course and operative management of this unusual but significant postoperative complication.